2020
DOI: 10.1177/0003319720958556
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil to Lymphocyte Ratio (NLR) Is Associated With Residual Syntax Score in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: The neutrophil to lymphocyte ratio (NLR) predicts adverse clinical outcomes in several cardiovascular diseases. Our aim was to investigate the association of residual SYNTAX score (rSS) with the NLR in patients (n = 613) with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention. Patients were divided into 2 groups: group 1 with low NLR (<2.59) and group 2 with high NLR (>2.59). Coronary artery disease severity was calculated for both groups besides base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Ching-Hui Sia et al retrospectively analyzed the data from 289 post-AMI patients with left ventricular thrombosis and found that NLR was an important predictor of thrombus resolution after AMI ( 24 ). A retrospective study including 613 STEMI patients found NLR was positively associated with residual SYNTAX score (rSS), and NLR > 2.59 was an independent predictor of increased rSS ( 25 ). These results all support NLR as having an effective predicting ability of poor outcomes and severe conditions of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Ching-Hui Sia et al retrospectively analyzed the data from 289 post-AMI patients with left ventricular thrombosis and found that NLR was an important predictor of thrombus resolution after AMI ( 24 ). A retrospective study including 613 STEMI patients found NLR was positively associated with residual SYNTAX score (rSS), and NLR > 2.59 was an independent predictor of increased rSS ( 25 ). These results all support NLR as having an effective predicting ability of poor outcomes and severe conditions of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…A study also proved that NLR is an independent predictor of no reflow and an indicator of hospitalization and long-term prognosis 9 . In STEMI patients, NLR is an independent predictor of high residual SYNTAX score and an independent predictor of the severity of coronary artery disease after PCI 10 . Among the 60,087 participants in five contemporary randomized trials, NLR consistently predicted future cardiovascular events and all-cause mortality 11 .…”
Section: Introductionmentioning
confidence: 95%
“…2-6 Increased blood neutrophil count and neutrophil to lymphocyte ratio (NLR) have been reported be related with the presence, severity, and outcome of coronary artery stenosis. 7-9…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Increased blood neutrophil count and neutrophil to lymphocyte ratio (NLR) have been reported be related with the presence, severity, and outcome of coronary artery stenosis. [7][8][9] There are significant differences in neutrophil count and NLR between males and females, and between premenopause and post-menopause stages in females. [10][11][12] Moreover, in females, the reproductive events, such as puberty, the age at menopause, and childbearing and breastfeeding histories affected the white blood cell (WBC), neutrophil, and lymphocyte counts.…”
Section: Introductionmentioning
confidence: 99%